Analisis Kecepatan Perambatan Gelombang Internal Soliter di Selat Lombok dengan Citra Himawari-8 - Chonnaniyah Chonnaniyah; I Wayan Gede Astawa Karang; Abd. Rahman As-syakur; Takahiro Osawa (Fakultas Kelautan dan Perikanan Universitas Udayana, 2022)
Internal waves are phenomena that occur below sea surface. One of the most observed types of internal waves was called a solitary wave or soliton so it is often known as an internal solitary wave (ISW). Lombok Strait was one of the straits located in the southern part of the Indonesian archipelago which has the characteristics of intensive ISW generation because this strait has complex waters characteristics. This study aim to analyzed in detail the changes in the ISW propagation speed at the first crest soliton every 10 minutes using Himawari-8 data. The detected ISW pattern is then extracted at the first crest of the soliton as a reference to measure the distance between the detected soliton every 10 minutes as input in estimating the propagation speed. The Himawari-8 image which was in this study detected 2 ISW packets in the Lombok strait area. Packet 1 which was detected in the northern part of the Lombok strait approaching Kangean island had a group speed of 2.22 m/s and Packet 2 which was detected in the area around the Lombok strait had a group speed of 2.78 m/s. The difference in group velocity of the two packets is due to the variation in depth along the ISW propagation. The analysis results of changes in ISW propagation speed in this study indicate that Himawari-8 imagery is a very effective instrument for analysing changes in ISW propagation speed in detail every 10 minutes which is difficult for satellite imagery which usually has low temporal resolution.